Un document: Deziluziile mele în Rusia - Emma Goldman; Cristina Deutsch (Revista de Istorie și Teorie Literară)
Emma Goldman (27th of June 1869 – 14th of May 1940), also known as Red Emma, was a well-known anarchist of Lithuanian origin famous in the United States and in Europe for her discourses and writings. Blamed by the adversaries for supporting the politically motivated murder idea and violent revolution and admired by her fans as being a model of the feminist rebel, Goldman played a decisive role in developing the anarchist political philosophy in the United States during the first half of the XXth century. In 1893, she was put in Blackwell Island’s jail for instigation to revolt when she publicly addressed to the unemployed workers, urging them to put into practice the expropriation idea, a concept quite new in those times, took over from Kropotkin. In 1901, she was arrested again, together with nine other anarchists, because of the murder attempt organized by Leon Czolgosz, an insurrectionist who had shot President McKinley. Nevertheless, she is exonerated and released. In 1906, she publishes, together with Alexander Berkman, Mother Earth, a magazine with a feminist-anarchist orientation, publishinging both Nietzsche’s writings and Leo Tolstoy’s essays, both of them having a major influence upon her ideas. In 1908, American citizenship has been retired to her and in 1914, together with Berkman, she participates to violent street meetings against John D. Rockefeller, an activity concluded with a murder attempt against him; as a consequence, Goldman leaves for San Francisco where she starts her own magazine, The Blast. At the beginning of 1916, she will be arrested again under the accuse of delivering leaflets containing material that has as a subject birth control. In prison, she becomes good friend with Gabriella Segata Antolini, Luigi Galleani’s famous disciple, whom she will personally meet later on. In 1917, she is arrested again and condemned, this time because of her opposition to the United States’ participation to the First World War. Deported in Russia in 1919, she will describe this experience in “My Disillusionment in Russia” and “My Further Disillusionment in Russia”. In 1921 she manages to escape, going to England, where she will be a target for criticism coming from all the European and American leftists refusing to see the truth of the total failure of the Russian Revolution. In addition, she has been living in France for a while, being a close friend of Peggy Guggenheim. In 1936, she leaves for Spain in order to support Spanish Republic against General Franco’s insurgence, publishing in here the weekly CNT-FAI Information Bulletin, but being also present on the Aragon, Valencia, and Madrid fronts. From her works, we mention: Anarchism and Other Essays (1911), The Social Significance of Modern Drama (1914), Living My Life (first volume–1931, second volume – 1933), My Disillusionment in Russia (1922), My Further Disillusionment in Russia (1924).